A Novel Lipidomics Approach to Predicting Pulmonary Hypertension in Human Heart Failure (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF To see the formatted meeting abstract.
Keywords: Cardiology; Research